Children friendly masjid: physical layout and perspective of children and families - Abu Bakar, Aniza; Mohd Bohori, Nur Ayuni; Azmi, Mohamad Hafis (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Children friendly masjid is a concept of masjid design that welcomes children and their families. Masjid is one of the important institutions to know and love Allah SWT, gain knowledge, empower, and unite the ummah. However, the current masjid design may have overlooked on the needs of children and their family as can be seen from several masjid design guidelines such as the Garis Panduan dan Peraturan bagi Perancangan Bangunan 2015 from Jabatan Perdana Menteri (JPM), Deraf Garis Panduan Perancangan Masjid dan Surau 2011 from Jabatan Perancangan Bandar dan Desa Semenanjung Malaysia (JPBD), and the Architecture and Asset Management of Masjid from Malaysian Standard (MS2577:2014). The implication of these guidelines possibly causes the current design of masjid that might be less children friendly. Hence, it could lead to the discouragement for this group of people in coming to the masjid. Muslim youth can be shaped with good morality if they become close and familiar to masjid at the earliest stage. This study aims to identify the holistic design approach of masjid that addresses the needs of families with young children mainly. Taking the Masjid Al-Ridhuan (MAR), Hulu Kelang as the case study site, the spatial arrangement of the masjid, the behavior of children and their space utilization, and the perspective from the parents and children regarding the needs on spaces at the masjid are being identified by applying methods such as site inventory, observation, and a semi-structured interview. The finding indicates that MAR demonstrates some criteria for a children friendly environment. This study offers new insights into formulating new design approach and guideline towards children friendly masjid (CFM).